2006
DOI: 10.1143/jpsj.75.074705
|View full text |Cite
|
Sign up to set email alerts
|

Search for Magnetic Excitation Spectra of NaxCoO2·yD2O –Neutron Scattering–

Abstract: Neutron inelastic scattering studies on aligned crystals of Na x CoO 2 ⋅yD 2 O have been carried out. Significant scattering has been observed for phonons originating from the vibrations of the short-range ordered D 2 O molecules. No firm evidence for the magnetic fluctuations has been found for the Na x CoO 2 ·yD 2 O, while the very weak intensity modulation observed in the scans along (1/2, 1/2, l) suggests the existence of the antiferromagnetic fluctuations in the non-deuterated parts of the sample, the vol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…1.3D 2 O no signals of magnetic fluctuations were detected. 14) The results obtained by the present authors' group contradict the idea of the exotic superconductivity, but seem to be consistent with the phonon-mediated superconductivity proposed by Yada and Kontani. 15) In the present work, we have carried out further studies of the magnetic properties of Na 0:3 CoO 2 .…”
Section: Introductionsupporting
confidence: 89%
“…1.3D 2 O no signals of magnetic fluctuations were detected. 14) The results obtained by the present authors' group contradict the idea of the exotic superconductivity, but seem to be consistent with the phonon-mediated superconductivity proposed by Yada and Kontani. 15) In the present work, we have carried out further studies of the magnetic properties of Na 0:3 CoO 2 .…”
Section: Introductionsupporting
confidence: 89%
“…(The peaks around h ¼ 0.5 is the contribution of the motions of the intercalated D 2 O.) [7]. These results are consistent with the fact that the Cooper pairs are in the singlet state.…”
supporting
confidence: 78%
“…Inelastic neutron scattering studies have also been carried out [7] on aligned crystals of Na x CoO 2 Á yD 2 O, which contains the superconducting bilayer (y$1.3) phase and the non-superconducting monolayer (y$0.6) and nondeuterated (y ¼ 0; x$0.44 from the c value) phases, where the volume fractions of these phases are 0.64, 0.10, and 0.24, respectively. In the studies, weak spin fluctuations (not shown) have been detected at Q points in the reciprocal space of the non-deuterated part, which correspond to both intra-plane and inter-plane antiferromagnetic correlation.…”
mentioning
confidence: 99%
“…59 Co-NMR and NQR measurements have been carried out using conventional coherent pulsed-NMR methods. The Na 0.7 CoO 2 single crystals were prepared by the floating zone method 10) and then Na de-intercalation and H 2 O intercalation were carried out as described before. 3) The obtained single crystals were confirmed to have the ν Q3 -values of ~12.7 MHz by NQR measurements, indicating that it is in the large-ν Q3 superconducting regions of the T-ν Q3 phase diagram shown in Fig.…”
mentioning
confidence: 99%